Survival Strategies for Electracoustic Music - Copeland, Darren (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2003)
The paper outlines, from the author's perspective as composer and event producer, the importance of community relations in building a larger audience and gaining more relevance for electroacoustic music in the century ahead.